(x+2)(x+1) = x^2 + 1x + 2x + 2 = x^2 + 3x +2
Chat with our AI personalities
If you mean: x2+3x+2 then it is (x+1)(x+2) when factored
If you factor x2 - 3x - 10, you'll get (x-5) (x+2). If your equation is x2 - 3x -10 = 0, then x = 5, and x = -2.
x2 + 3x - 40 = (x + 8)(x - 5)
x2 - 3X - 10 = (X - 5)(X + 2)So, (X2 - 3X -10) / (X-5) = X + 2
x2 + 3x + 28 can not be factored. If on the other hand you meant to type: x2 + 3x - 28 That can indeed be factored: = x2 + 7x - 4x - 28 = x(x + 7) - 4(x + 7) = (x - 4)(x + 7)